(untitled) (La Rivada, 2025)
Based on an online survey conducted with prospective teachers in Badajoz (Spain) and Posadas (Argentina), this article explores multilingual competences and forms of intercultural education beyond national boundaries. The quantitative data obtained show that in both cities, the majority of prospective teachers consider knowledge of other countries’ educational systems, the inclusion of bi- or multilingual teaching resources, and the integration of intercultural topics as important or very important. In addition, many future education professionals possess intercultural capital which could be applied in different national and transnational contexts of intercultural teaching and learning. However, in order to fully harness this potential, it is crucial to create more equitable and inclusive educational contexts that seek to overcome systematic imbalances in opportunities for the realization of intercultural capital.